Indoor light energy harvesting technique to energize a heat sensor using polycrystalline solar panel - Syazana Izzati Razali, Nur; Hajar Yusoff, Siti; Liza Tumeran, Nor; Sharir Fathullah Mohd Yunus, Muhammad (Institute of Advanced Engineering and Science, 2023)
This paper presents the effect of using different illumination types between the polycrystalline solar panel and the light sources on energy harvesting performance for indoor low-power applications such as heat sensors. The main advantage of indoor energy harvesting is it makes good use of ambient energy from the environment and converts it directly to electricity for small power devices. In this paper, the maximum power of polycrystalline solar panels for four different light illuminations has been investigated under different distances of light sources from the polycrystalline solar panel. Implementation and test results of the effect of varying the distance and the power produced for different light illuminations are presented which highlights the practical issues and limitations of the system.